Immunization information systems in Canada: Attributes, functionality, strengths and challenges. A Canadian Immunization Research Network study - Wilson, Sarah E. (Can J Public Health, 2016)
OBJECTIVES: Canada does not have a national immunization registry. Diverse systems to record vaccine uptake exist, but these have not been systematically described. Our objective was to describe the immunization information systems (MSs) and non-IIS processes used to record childhood and adolescent vaccinations, and to outline the strengths and limitations of the systems and processes. METHODS: We collected information from key informants regarding their provincial, territorial or federal organization’s surveillance systems for assessing immunization coverage. Information collection consisted of a self-administered questionnaire and a follow-up interview. We evaluated systems against attributes derived from the literature using content analysis. RESULTS: Twenty-six individuals across 16 public health organizations participated over the period of April to August 2015. Twelve of Canada’s 13 provinces and territories (P/Ts) and two organizations involved in health service delivery for on-reserve First Nations people participated. Across systems, there were differences in data collection processes, reporting capabilities and advanced functionality. Commonly cited challenges included timeliness and data completeness of records, particularly for physician-administered immunizations. Privacy considerations and the need for data standards were stated as challenges to the goal of information sharing across P/T systems. Many P/Ts have recently implemented new systems and, in some cases, legislation to improve timeliness and/or completeness. CONCLUSION: Considerable variability exists among NSs and non-IIS processes used to assess immunization coverage in Canada. Although some P/Ts have already pursued legislative or policy initiatives to address the completeness and timeliness of information, many additional opportunities exist in the information technology realm.